2023
DOI: 10.3390/jof9020172
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Search of Bioactive Secondary Metabolites from Fungi Triggered by Chemical Epigenetic Modifiers

Abstract: Genomic analysis has demonstrated that many fungi possess essential gene clusters for the production of previously unobserved secondary metabolites; however, these genes are normally reduced or silenced under most conditions. These cryptic biosynthetic gene clusters have become treasures of new bioactive secondary metabolites. The induction of these biosynthetic gene clusters under stress or special conditions can improve the titers of known compounds or the production of novel compounds. Among the inducing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…The crude extract of P03MB2 without treatment with epigenetic modifiers had weak anti-HIV activity compared to the treated crude extracts. Sodium butyrate is an epigenetic modifier which inhibits the histone deacetylase activity, leading to the differentiation of the eukaryotic cells [ 86 , 87 ]. Previous studies showed that sodium butyrate treatment had the highest induction rate of 22 cryptic secondary metabolites from endophytic Nigrospora sphaerica [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crude extract of P03MB2 without treatment with epigenetic modifiers had weak anti-HIV activity compared to the treated crude extracts. Sodium butyrate is an epigenetic modifier which inhibits the histone deacetylase activity, leading to the differentiation of the eukaryotic cells [ 86 , 87 ]. Previous studies showed that sodium butyrate treatment had the highest induction rate of 22 cryptic secondary metabolites from endophytic Nigrospora sphaerica [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that sirtuin has not been identified in A. terreus or most other filamentous fungi. Previous results showed that nicotinamide, a potent inhibitor of sirtuins, significantly changed the metabolite profile of filamentous fungi [ 26 ]. Additionally, the effect was observed in A. terreus RA2905.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of these marks, the gene clusters are activated, altering the chromatin structure accordingly. Therefore, altering the histone modification state can regulate gene expression and induce numerous changes in metabolite spectra, ultimately activating the recessive secondary metabolite production [66,67].…”
Section: Epigenetic Regulations Of Secondary Metabolism In a Oryzaementioning
confidence: 99%